Vascular endothelium state in different types of antihypertensive treatment - N. V. Kucherenko; O. V. Nastradin; E. V. Eliseeva; E. S. Potapova; V. A. Nevzorova (Кардиоваскулярная терапия и профилактика)
Aim. To study ozone therapy effects on blood biochemistry (NO metabolites, NOn-), pro6oxidant and anti-oxdant  systems in arterial hypertension (AH) patients.Material and methods. The study was focused on ozone therapy effects on metabolic activity of vascular endothelium and lipid peroxidation (LP) activity in 126 patients with stage I-II AH. The levels of NOn- in serum, malone dialdehyde in plasma and superoxide dismutase in red blood cells were measured.Results. In Stage I-II AH, NOn- concentration was reduced, especially in Stage II AH. After one-month combined treatment, plasma NOn- level was similar to that in controls. As early as after first 7 days, ozone therapy resulted in significant LP activity reduction and increased antioxidant potential (AOP), comparing to standard treatment group.Conclusion. Ozone therapy facilitates normalization of vascular endothelium NO-producing function, decrease in LP activity, and AOP restoration.